2018
DOI: 10.3892/ijmm.2018.3892
|View full text |Cite
|
Sign up to set email alerts
|

Potential regulatory role of circular RNA in idiopathic pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive type of interstitial pneumonia with unknown causes, poor prognosis and no effective therapy available. Circular RNAs (circRNAs), which serve as potential therapeutic targets and diagnostic biomarkers for certain diseases, represent a recent hotspot in the field of RNA research. In the present study, a total of 67 significantly dysregulated circRNAs were identified in the plasma of IPF patients by using a circRNA microarray. Among these circRNAs, 38 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 51 publications
(51 reference statements)
0
58
0
Order By: Relevance
“…By contrast, lncRNAs such as lncCHRF, n341773 and H19 contribute to lung fibrosis by acting as miRNA sponges . Based on our previous studies, competing endogenous RNAs are present not only in lncRNAs but also in circRNAs . In this study, we showed the existence of competing endogenous RNAs under drug action.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…By contrast, lncRNAs such as lncCHRF, n341773 and H19 contribute to lung fibrosis by acting as miRNA sponges . Based on our previous studies, competing endogenous RNAs are present not only in lncRNAs but also in circRNAs . In this study, we showed the existence of competing endogenous RNAs under drug action.…”
Section: Discussionmentioning
confidence: 61%
“…Each bar represents the mean ± SD, n = 6, *P < .05, **P < .01 circRNAs. 19,43 In this study, we showed the existence of competing 47 Lee et al analysed the transcriptome complexity through RNA sequencing in normal and failing murine hearts. 48 However, few studies have identified the profiles of differentially expressed circRNAs under drug action using RNA sequencing in progressive lung fibrosis.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations